SISTEM PENGATUR TIMER MEKANISME DAN SUHU PADA ALAT PENGASAPAN IKAN - Waode Dela Safitri; Dody Chandra Kumara; Wirdha Wirdha; Sary Widyaningsih; Moh. Gazali (Foristek, 2022)
This research aims to facilitate a more even fish maturation process due to the rotation process of the fish rack which is regulated by the system in Mechanism Timer and Temperature at the Fish Smoking machine. The smoking machine can also make it easier for people to smoke fish. It has an overall height of 150 cm, door height of 110 cm, Fuel tank height of 30 cm, and foot height of 10 cm, in the fish smoking room there are 2 fish tray racks. The fuel for the smoking machine uses coconut husk and the coconut shell is equipped with a Digital Thermostat to read the temperature in the room and is also equipped with a Thermohygro to read the humidity in the room. The working principle of this tool is that the first step is to connect the multi-plug to the power source, from the power source to the MCB, the MCB gets current and when the MCB is turned on, the current enters the Push Button Switch, and when the Push Button On is pressed, the red light turns on, indicating there is the current that enters the Digital Thermostat digital from the Thermostat to the plug terminal, from the plug terminal to the Timer and from the Timer to the Power Supply From the Power Supply changes the current from 220 volts to 12 volts when the green light is on then the Power Window functions by moving the fish rack tray.